USAID BERSAMA Project: Examining Gender-Based Violence Prevention in Eastern Indonesia (Case Study: Sentani District, Papua) - Lea Yarona (Papua Journal of Diplomacy and International Relations, 2021)
Almost all countries have undertaken a host of policies, public education, and action programs to reduce Gender-Based Violence (GBV), including Indonesia. This article aims to illustrate how GBV occurs in Indonesia’s Papua province, particularly in Sentani district; and how a project funded by USAID manages to create awareness in the area. This paper used a qualitative approach. The data collected from books, journals, web pages on the internet, as well as the author’s personal observation when becoming an assistant field officer of a local civil society organization partnering with the USAID BERSAMA Project. This article found that the Project has raised awareness of GBV in Sentani, and potentially resulted in behavior change. This can be seen from the commitment of some participants in the FGDs to change the way they treat each other; not to mention the grass-roots support from chiefs in the respective villages. Nevertheless, the project has weaknesses in implementation process: the modules used by CSOs did not suit the Papuan context in certain circumstances, the FGDs were in the short-run, and changing behavior was not an easy task. This study also found that social norms marketing could be the alternative approach to make changes concerning GBV in Sentani district.KEYWORDSGender-Based Violence; Sentani; USAID